Meanings of the Qur’anic near-synonyms: al-ṣirāṭ and al-sabīl (the path) and their English translations - Abdul-Ghafour, Abdul-QaderKhaleel; Norsimah Mat Awal; Intan Safinaz Zainudin; Ashinida Aladdin (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study investigates the meanings of the Qur’ānic near-synonyms اصراط al-ṣirāṭ and السبيل al-sabīl (the path) and their English translations. It aims to identify the contextual meanings of these near-synonyms based on the exegeses of the Holy Qur’ān. Then, it explains the differences in meaning between these near-synonyms and how such semantic differences are reflected in the English translations of the Holy Qur’ān. The RC-S approach by Murphy (2003) is adopted in this study as a theoretical framework for the analysis of data. The qualitative approach is also employed for collecting and analyzing the data of the study. Moreover, the exegeses of the Holy Qur’ān are consulted to find out the semantic differences between the selected near-synonyms. The results of the study reveal that there are some differences in the denotative and connotative meaning between the Qur’ānic near-synonyms and that the differences in meaning between both near-synonyms are not reflected in the English translations. The study provides recommendations for readers and translators especially the translators of the Holy Qur’ān.